2020
DOI: 10.1021/acs.accounts.0c00403
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Materials and Molecules

Abstract: The visualization of data is indispensable in scientific research, from the early stages when human insight forms, to the final step of communicating results. In computational physics, 1 chemistry and materials science, it can be as simple as making a scatter plot, or as straightforward as looking through the snapshots of atomic positions manually. However, as a result of the "big data" revolution these conventional approaches are often inadequate. The widespread adoption of high-throughput computation for mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 50 publications
2
115
0
Order By: Relevance
“…The SOAP formalism has been applied in structural analyses of a variety of materials 74 , including alloyed Sb 2 Te 3 19 , and in the fitting of machine learning interatomic potentials (ref. 75 and references therein) including one for liquid, amorphous, and crystalline Ge 2 Sb 2 Te 5 76 .…”
Section: Soap Structural Analysismentioning
confidence: 99%
“…The SOAP formalism has been applied in structural analyses of a variety of materials 74 , including alloyed Sb 2 Te 3 19 , and in the fitting of machine learning interatomic potentials (ref. 75 and references therein) including one for liquid, amorphous, and crystalline Ge 2 Sb 2 Te 5 76 .…”
Section: Soap Structural Analysismentioning
confidence: 99%
“…1, where we use a new method to embed high-dimensional data in two dimensions, based on a hierarchical combination of cluster-based data classification and multidimensional scaling [34,35]. This is a popular tool for visualizing structural databases in the context of ML applied to the study of atomic systems [36][37][38][39].…”
Section: A C60 Gap Force Fieldmentioning
confidence: 99%
“…To interpret (cg-) SOAP analysis results, the dataset is often visualized as a two-dimensional projection. 29,32,39 A large number of algorithms are available to carry out this projection (or "embedding"), and a central aspect of the present work will be to compare different widely used embedding schemes. Our implementation stores the similarity of all structures with one another in the form of a symmetric similarity matrix, K, which we construct using the per-cell averaged similarity (Eq.…”
Section: Dimensionality Reduction and Visualizationmentioning
confidence: 99%
“…28 Subsequently, it was shown how similarity kernels based on the SOAP formalism may be used to analyze the structural similarity for molecular and bulk periodic structures. 29 By coupling to ML techniques such as dimensionality reduction and data clustering, one can begin to navigate complex configurational spaces, [30][31][32] and search for underlying structure-property relationships. [33][34][35][36][37][38] We have recently demonstrated that a combination of coarse-graining, re-scaling, and SOAP analysis enables geometric comparison between very different classes of materials, exemplified us-ing a database of AB 2 hybrid and inorganic networks.…”
Section: Introductionmentioning
confidence: 99%